The Effect of Intellectual Capital Components on Financial Performance of Islamic Commercial Banks in Indonesia - Diani, Treska Melsa; Nugroho, Lucky (LifeSciFi, 2025)
Islamic commercial banks in Indonesia have grown rapidly, yet their profitability remains lower and more volatile than that of conventional banks. This condition raises questions about the role of intellectual capital in creating sustainable financial performance. This study aims to examine the effect of value added capital employed, value added human capital, and value added structural capital on the financial performance of Islamic commercial banks in Indonesia over the period 2015–2024. The research used a quantitative approach with monthly data from all Islamic commercial banks registered with the Financial Services Authority of Indonesia. Data were analyzed using multiple linear regression after fulfilling classical assumption tests and handling outliers. The results show that the three components of intellectual capital simultaneously have a significant effect on return on assets and explain 88.9 percent of its variation. Partially, value added capital employed and value added human capital have a significant negative effect, while value added structural capital has a significant and strongly positive effect. These findings indicate that during the observation period, rapid asset expansion and high human capital costs tended to reduce short-term profitability, whereas investment in systems, technology, and organizational infrastructure became the main driver of profit growth.